مسارات التنويع الاقتصادي والتنمية المستدامة في دول نفطية مختارة: دراسة تحليلية - شنجار آل عيسى, عبدالكريم جابر (جامعة الوادي - University of Eloued, 2021)
In light of this new global crisis, all countries of the world, whether developed or emerging and developing or transforming, found themselves facing a severe shortage of medical supplies and devices. To the extent that the US President reached the point of asking (GENARAL MOTORS) company specialized in the automotive industry to equip hospitals and medical centers with artificial respirators, then everyone went to the point that the concept of economic diversification is not limited to neglecting any aspect of economic activities, no matter how little added value is in perceptions Monopoly profits of global companies. And if this is the case for developed countries, then how is it the case for less developed countries, including developing countries that were looking at The issue of economic diversification routinely. On this basis, this study believes that the process of adopting this issue must be according to real, serious and fateful visions, as it is a dynamic state accompanying the economic, political and even social transformations that are taking place in the world.
Paths of economic diversification and sustainable development in oilproducing countries Selected : an analytical study
مقال
Keywords: (التنويع الاقتصادي ،التصنيف الدولي لهيكل السلع والخدمات ، التنمية المستدامة ، رؤية2021، رؤية 2030)